Predicting EFL Learners' Reading Comprehension Score from Reading Anxiety and Motivation - Hidayati, Nurul (Universitas Al-Amien Prenduan, 2018)
Language requires some skills such as reading, writing, listening, and speaking that may use in communication. In language teaching English reading has always been considered one of the most important parts of foreign/second language learning. Based on previous empirical researches, this study emphasizes to predict EFL learners’ reading comprehension from reading anxiety and motivation. The subject of the study was all the accessible population because the number of the sample is quite small so the researcher takes all the sample of the population. The units used in this research were English department students at University of Madura (UNIRA). Data were collected using questionnaire from 100 students of English department in University of Madura and analyzed using Multi Linier Regression program in SPSS 20 version for windows. The major findings include first, Reading anxiety have negative significant correlation on EFL learners in reading comprehension. Second, Motivation has positive significant correlation on EFL learners in reading comprehension. And third, Reading Anxiety and Motivation have significant correlation with EFL learners’ in reading comprehension simultaneously. Therefore, when the learners have high motivation their anxiety will decrease and learners will get better score. Those finding suggests one impact the other, so there is a need to incorporate motivation (intrinsic and extrinsic) to improve EFL learner’s reading comprehension being well then anxiety still in controlled.